PyOpenMS: A Python‐based interface to the OpenMS mass‐spectrometry algorithm library. Issue 1 (13th January 2014) - Röst, Hannes L.; Schmitt, Uwe; Aebersold, Ruedi; Malmström, Lars
Abstract : pyOpenMS is an open‐source, Python‐based interface to the C++ OpenMS library, providing facile access to a feature‐rich, open‐source algorithm library for MS‐based proteomics analysis. It contains Python bindings that allow raw access to the data structures and algorithms implemented in OpenMS, specifically those for file access (mzXML, mzML, TraML, mzIdentML among others), basic signal processing (smoothing, filtering, de‐isotoping, and peak‐picking) and complex data analysis (including label‐free, SILAC, iTRAQ, and SWATH analysis tools). pyOpenMS thus allows fast prototyping and efficient workflow development in a fully interactive manner (using the interactive Python interpreter) and is also ideally suited for researchers not proficient in C++. In addition, our code to wrap a complex C++ library is completely open‐source, allowing other projects to create similar bindings with ease. The pyOpenMS framework is freely available athttps://pypi.python.org/pypi/pyopenms while the autowrap tool to create Cython code automatically is available athttps://pypi.python.org/pypi/autowrap (both released under the 3‐clause BSD licence).